Gene therapy for lung inflammatory diseases: not so far away?. Issue 8 (August 1997) - Sallenave, J M; Porteous, D J; Haslett, C
Abstract : The lung is a readily accessible target organ for gene therapy. To date, therapeutic gene delivery has largely focused on introducing functional, corrective genes in lung diseases arising from single gene defects such as cystic fibrosis. More recently interest has centred on gene therapy as a potential therapeutic tool in modulating complex pathological processes such as pulmonary inflammation. Genetic modification of critical components of the inflammatory process may be beneficial-for example, overexpressing anti-elastase genes may circumvent elastase mediated lung damage in emphysema. With the development of improved viral and liposome vectors and the evolution of effective adjuvant immunosuppression to obviate host immune responses--for example, using selective cytokines and blockers of T cell surface activation--the potential exists to target therapeutic doses of transgene to deficient or dysregulated cells. Furthermore, increased understanding of tissue-specific promoter regions and of mechanisms controlling regulation of gene expression offer the potential for close control of therapeutic gene expression within the lung. Continuing refinements in these technologies will provide new therapeutic strategies in inflammatory lung disease.